Foraminifera Trace Anthropogenic CO2 in the NW Atlantic by 1950. Issue 24 (18th December 2019) - Mellon, Stefanie; Kienast, Markus; Algar, Christopher; de Menocal, Peter; Kienast, Stephanie S.; Marchitto, Thomas M.; Moros, Matthias; Thomas, Helmuth
Abstract: The Northwest Atlantic is a region of major climate change over the twentieth century, affected by the weakening of the Atlantic meridional overturning circulation. To assess whether the ability of this region to absorb anthropogenic CO2 has been impacted by this change, we present the region's first long‐term carbon isotope (δ 13 C) time series of fossil foraminifera spanning the past 4, 000 years. These records reveal an unprecedented negative δ 13 C excursion driven by anthropogenic CO2 penetration into the surface ocean, the "Suess effect" signal. This signal (amplitude −0.45‰) emerges in 1950 CE ± 15 with a decrease rate of 0.009 ± 0.001‰/yr. This marine signal is ~30% of the atmospheric Suess effect and emerges over a century later. Based on current estimates of the ratio of δ 13 CDIC change to dissolved inorganic carbon change and limited constraints on surface ocean residence times, we calculate a mean anthropogenic CO2 uptake rate of 0.6 ± 0.2 μmol/(kg yr) from 1950 to 2005. Plain Language Summary: Since the industrial revolution, the burning of fossil fuels for human energy and transportation needs has caused an accumulation of carbon dioxide (CO2 ) in the atmosphere. Over the same time period, nearly 30% of CO2 emissions have been taken up by the ocean. This absorption is not uniform; therefore, understanding local CO2 uptake rates is essential for assessing future ocean acidification risk. Our study investigates and presents the first long‐term history of carbon for the Northwest Atlantic shelf region. The CO2 emitted from fossil fuel burning has a distinct carbon isotope ratio compared to the preindustrial background level. Organisms called foraminifera incorporate the carbon isotope ratio of ocean carbon into their shells, which eventually sink to the seafloor where they are preserved in the sediments. For our analysis, we collected five sediment cores containing foraminifera from the NW Atlantic, resulting in carbon isotope records that span the last 4, 000 years. We find evidence of fossil fuel‐derived CO2 in the NW Atlantic starting in 1950 and translate carbon isotope trends into estimates of fossil fuel CO2 uptake rates by the surface ocean. Results from our study can be used to assess and predict future ocean acidification risk. Key Points: We present the first long‐term stable carbon isotope time series for the NW Atlantic shelf region Foraminifera reveal an unprecedented negative carbon isotope excursion, the Suess effect, driven by anthropogenic CO2 penetration into the surface ocean The regional Time of Emergence of the Suess effect is 1950 CE ± 15 years